2022
DOI: 10.3390/healthcare10060997
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between Socioeconomic Status and Incidence of Hysterectomy Using Data of the Korean Genome and Epidemiology Study (KoGES)

Abstract: Hysterectomy remains a frequent gynecologic surgery, although its rates have been decreasing. The aim of this study was to investigate whether socioeconomic status affected the risk of hysterectomy in Korean women. This prospective cohort study used epidemiologic data from 2001 to 2016, from the Korean Genomic and Epidemiology Study (KoGES). Multivariate logistic regression analyses were performed to estimate the association between household income or education level and hysterectomy. Among 5272 Korean women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Another study conducted in Korea similarly concluded that patients with lower income were more likely to undergo a hysterectomy because of the delay in seeking medical treatment, because conservative approaches are more readily available to individuals with higher income, and because of the perception among individuals with lower income that hysterectomy is a cheaper and safer option. 32 This is in the context of new, uterus-sparing alternatives. Nevertheless, given the limited data and incidence of hysterectomy in our study, these findings are unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Korea similarly concluded that patients with lower income were more likely to undergo a hysterectomy because of the delay in seeking medical treatment, because conservative approaches are more readily available to individuals with higher income, and because of the perception among individuals with lower income that hysterectomy is a cheaper and safer option. 32 This is in the context of new, uterus-sparing alternatives. Nevertheless, given the limited data and incidence of hysterectomy in our study, these findings are unreliable.…”
Section: Discussionmentioning
confidence: 99%